Factors Affecting Contractor’s Risk Attitude from Malaysia Construction Industry Perspective - Taofeeq, D. M.; Adeleke, A. Q.; Hassan, A. K. (International Society for Everant Publisher, 2019)
Risks always lead to the failure of the contractor to complete projects on time. This situation is caused by many factors. The contractor’s failure to plan, manipulate, perform, monitor, control and take into account all factors and risks involved may not guarantee the success of a project. In order to improve performance in Malaysia construction industry, the introduction of OSH Act 1994 have made all industry in Malaysia to identifying hazards, conducting a risk assessment and controlling those risk and at the same time implementing an integrated system to ensure consistency and better performance of projects in Malaysia industry. A total number of ninety-five (95) risk factors that are dampening and affecting contractor productivity in Malaysia construction industry were revealed by the ranking of the contractor risk attitude factors through SPSS. In the same vein, the risk factors were further classified into six (6) subclasses depending on their nature and likelihood of occurrence. Such as (Technical risk, Logistical risk, Management risk, Social-political risk, financial risk, and Environmental risk). In order to achieve the proper response rate for this study, in total 250 questionnaires were distributed to the construction industry in Kuantan Malaysia randomly. Of the 250 questionnaires distributed, 234 questionnaires were received with an equal percentage of 93.6%. Conversely, 7 questionnaires were found to be unusable due to missing data or provided the same responses to all the questions. Thus overall, 90.8% of the total questionnaires were usable concluding with an effective sample of 227. Statistical Package for Social Science (SPSS) version 21.0 for MS Window was used to analyse the collected data. The demographic profile of the companies and respondents were analysed with descriptive statistics. This study also focused on the G7 contractors operating in Malaysia construction industry that specialise in building, bridge and road construction project.